Member states of the Caribbean Community : schedule of specific commitments for the removal of restrictions on - the right of establishment provision of services and movement of capital under Protocol II amending the Treaty Establishing the Caribbean Community ([Caricom Secretariat] [Georgetown]GY, 2002)
Tabulates the programmes for the removal of restrictions in CARICOM Member States.
Keywords: SERVICE INDUSTRY